Production of Vowels and Nuclear Accents by Chilean Learners of English as a Foreign Language - Grau-Morales, X; Del Saz-Caracuel, M (Universidad de Concepcion, 2022)
Previous studies show that L2 segments are easier to acquire than suprasegments. In an EFL context, the L1 influence seems to be minimized as learners gain L2 experience. Our study explores the effect of L1 transfer from Spanish and L2 experience in English on the production of vowels and nuclear accent, by comparing acoustically the productions of elementary and advanced learners of EFL in Chile. Results indicate improvement with higher L2 experience, although still far from native speakers. Concerning vowels, certain problems with tongue advancement and height persist at advanced levels, with overreliance on intensity to produce tense vowels. Regarding nuclear accents, correct nucleus placement improves with experience, and productions start to reflect the acoustic correlates of one English variety, still with a tendency to over rely on duration to mark the nucleus. Further research is warranted, such as on rhythm and fluency, to have a more holistic understanding of the effects of L1 transfer and L2 experience on L2 English. © 2022 Universidad de Concepcion. All rights reserved.